2003
DOI: 10.1046/j.1535-7597.2003.03208.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y and Epilepsy

Abstract: It is a central tenet of the epilepsy field that seizures result from the imbalance of excitation over inhibition (1). The bulk of excitation is mediated by the neurotransmitter glutamate, whereas inhibition results mainly from the actions of ␥ -aminobutyric acid (GABA).europeptide Y (NPY) is a 36-amino acid peptide made by neurons throughout the brain and by other secretory cells of the body. NPY has been associated with a number of physiologic processes in the brain, including the regulation of energy balanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 53 publications
3
48
0
1
Order By: Relevance
“…A large body of information provided evidence that exogenously applied NPY has anti-epileptic activity in both in vitro models (bursting without Mg 2+ , picrotoxin and stimulus-train induced bursting in hippocampal slices), and in vivo models of partial seizures such as different kindling models and kainate-induced seizures reviewed previously [60,61]. Although less extensively studied, NPY may also be beneficial in models of generalized seizures, the pentylenetetrazole [62] and the electroconvulsive seizures [63], and models of absence epilepsy [28].…”
Section: Neuropeptide Ymentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of information provided evidence that exogenously applied NPY has anti-epileptic activity in both in vitro models (bursting without Mg 2+ , picrotoxin and stimulus-train induced bursting in hippocampal slices), and in vivo models of partial seizures such as different kindling models and kainate-induced seizures reviewed previously [60,61]. Although less extensively studied, NPY may also be beneficial in models of generalized seizures, the pentylenetetrazole [62] and the electroconvulsive seizures [63], and models of absence epilepsy [28].…”
Section: Neuropeptide Ymentioning
confidence: 99%
“…There are 4 different neuropeptide receptors identified in human, Y1, Y2, Y4 and Y5, of which Y1, Y2 and Y5 may be involved in epilepsy [61]. These receptors signal through G i proteins that inhibit adenylate cyclase and decrease intracellular Ca 2+ levels [69].…”
Section: Neuropeptide Ymentioning
confidence: 99%
“…In models of temporal lobe epilepsy (TLE), increased NPY mRNA and protein expression has been demonstrated in neocortical and limbic regions, particularly in GABAergic inhibitory interneurons and following its de novo synthesis in dentate granule cells and transport through mossy fibers to their terminals (Causing et al, 1996;Gruber et al, 1994;Marksteiner et al, 1989Marksteiner et al, , 1990Marksteiner and Sperk, 1988;McCarthy et al, 1998;Schwarzer et al, 1995;Tu et al, 2005). In the epileptic brain, presynaptic release of NPY can reduce epileptiform discharges and inhibit hippocampal seizures (Colmers and El Bahh, 2003;Tu et al, 2005;Woldbye et al, 1996), whereas transgenic mice lacking endogenous NPY exhibit hyperexcitability at the cellular level and increased sensitivity to seizure activity (Baraban et al, 1997;DePrato Primeaux et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It regulates energy usage, and is involved in learning, memory processing, and epilepsy. 36 It has been shown that NPY is expressed in the mammalian myocardium and that it co-localizes with norepinephrine in perivascular sympathetic neurons. NPY is released together with norepinephrine during conditions of high sympathetic activity and it contributes to the regulation of myocardial contractility through NPY receptor type 1 and type 2.…”
Section: Resultsmentioning
confidence: 99%